Paradoks "Pahlawan Tanpa Tanda Jasa": Analisis Sosiologis Terhadap Rendahnya Minat Sarjana Pendidikan Berkarier Sebagai Guru - Muhammad Afrijaludin; Syauqi Liqo Irobbi; Rinesya Nabilah; Nifri Alifah; Abdul Fadhil (Advances In Education Journal, 2026)
This article analyzes the sociological paradox behind the declining interest of education graduates in pursuing teaching careers. Data from the Indonesian Ministry of Education (Kemendikbudristek, 2023) confirm that 1.6 million teachers have not received adequate incomes, and a survey by Dompet Dhuafa and IDEAS (2024) reveals that 74.3% of honorary teachers earn below Rp 2 million per month. Research by Hafidah et al. (2024) documented negative perceptions among education students toward the teaching profession, while OECD TALIS 2018 data show that only 26% of teachers globally feel valued in society. Using a qualitative literature review approach, this article applies Bourdieu's capital theory, Merton's social strain theory, and Parsonian structural functionalism to analyze these phenomena. The findings indicate that low welfare, inadequate social prestige, and bureaucratic burdens are the main drivers discouraging graduates from entering the teaching profession. Structural policy reform is urgently needed.